Does the in-packaging food preservation technique, retorting, affect the migration of food packaging? : a thesis presented in partial fulfilment of the requirements for the degree of Master of Engineering in Chemical Bioprocess Engineer at Massey University, New Zealand - Spencer, Hannah Joy (Massey University, 2024)
The effects of retort treatments on chosen monolayer plastic films commonly used in the food industry were studied. Changes occurring in the plastic monolayers and the leachates into the food system, and post-retort treatments were monitored. Three industry-relevant retort settings were trialled: 110 °C for 51 mins, 115 °C for 25 mins, and 121 °C for 16 mins. The monolayer plastic films studied were polyethylene, polyethylene terephthalate, and polyamide; common components of multi-layer retort pouches. The key areas for this research project were to investigate how different retort time-temperature profiles affect the monolayer physically and the overall and specific migration from monolayer films into different food simulants. This was used to determine whether a significant change in migration from the monolayer films was associated with retort processing. The plastic was tested using EU standards of compliance and using 10 % ethanol and 3 % acetic acid as food simulants to represent retort products. The materials were visually inspected straight after retorting, followed by an in-depth internal surface investigation to monitor changes via microscopy. The overall and specific migration was assessed, and compounds putatively identified were assigned a Cramer class. Overall, the retort treatment at 110° C for 51 mins created the most changes in terms of migration on most of the samples. The results of this research were for the simulants: ethanol triggered significantly more changes in PE and PET. For PA films the results revealed that both simulants had a similar number of changes, due to long processing time.
Figures 1 & 2 are reused with the respective publisher's permission.
Keywords: 300604 Food packaging, preservation and processing